Acculturating Discipline In The Aspect Of Obeying Rules In Learning PPKn In Elementary School - Syahelani, Jodhi Navella; Sutama, S; Adnan, Mazlini (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: The purpose of this research is to describe the discipline of obeying school rules and class rules in Civics (PPKn) learning. Methodology: This study uses a qualitative method with an ethnographic approach. The research subjects are principals, teachers, and students of Kradenan Grobogan 1 State Elementary School. Data were collected through observation, interviews, and document study, and analyzed using a flow technique. Results: The results show that Civics teachers play a role in fostering students’ self-awareness of school rules and use various strategies such as acting as motivators, correctors, and building peer support systems to develop students’ awareness of rules. Applications/Originality/Value: This research can be applied as a reference for Civics teachers and school principals to design effective strategies in fostering student discipline through supervision, motivation, and peer support. The findings also add practical insights for schools to strengthen school culture and group norms to improve students’ compliance with both classroom and school rule